2023
DOI: 10.3390/universe9030123
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Search for Axion-Like Particles by a Three-Beam Stimulated Resonant Photon Collider with Short Pulse Lasers

Abstract: Toward the systematic search for axion-like particles in the eV mass range, we proposed the concept of a stimulated resonant photon collider by focusing three short pulse lasers into a vacuum. In order to realize such a collider, we have performed a proof-of-principle experiment with a set of large incident angles between three beams to overcome the expected difficulty to ensure the space–time overlap between short pulse lasers and also established a method to evaluate the bias on the polarization states, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, it can be constructed using a combination of commercial products, hence having the advantage of flexibility for the design so that we can replace focusing mirrors as we need. As we demonstrated in the previous pilot search [21], we indeed found that it was necessary to prepare a space for a target holder at the focal point to ensure the spatiotemporal synchronization of three pulses, a camera system to record the beam profile, and a shielding wall to suppress background from beam remnants. This requires lots of flexibility including changing the focal length, which has an impact on the sensitivity.…”
Section: Basic Design To Realize Variable Collision Anglesmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, it can be constructed using a combination of commercial products, hence having the advantage of flexibility for the design so that we can replace focusing mirrors as we need. As we demonstrated in the previous pilot search [21], we indeed found that it was necessary to prepare a space for a target holder at the focal point to ensure the spatiotemporal synchronization of three pulses, a camera system to record the beam profile, and a shielding wall to suppress background from beam remnants. This requires lots of flexibility including changing the focal length, which has an impact on the sensitivity.…”
Section: Basic Design To Realize Variable Collision Anglesmentioning
confidence: 81%
“…In our previous study of a quasi-parallel collision system, we focused two lasers into the same optical axis and collided them at a shallow incident angle to search for ALPs in the sub-eV mass range [15][16][17][18][19]. Recently, we have proposed and demonstrated a pilot search for heavier ALPs based on a three-beam stimulated resonant collider ( t SRPC) [20,21]. In the near future, we plan to search for ALPs by continuously changing collision angles in the eV mass range.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, both theoretical and experimental studies of dark matter are described. In particular, quark-nugget dark matter [65][66][67] and axion-like particles [68][69][70] are investigated. After that, the subjects of dark energy [71,72] and modified gravity theories [73] are explored.…”
mentioning
confidence: 99%
“…In Ref. [69], a pilot survey of particles like axions is performed using a photon collider. The photon collider is used for the resonance of the stimulation, and it has three beams with the lasers emitting short pulses.…”
mentioning
confidence: 99%
“…Figure50: Summary of current bounds and prospects of ongoing and future searches for the axion-photon coupling. Regions shaded in colours correspond to experiments: mauve for laboratory[498,499,706,707,713,714,715] and collider[703,741,185,742,743,185,744,745,746,747,748,749,749,750,751] searches for axions, green for searches for solar axions[236,158], and blue for direct dark matter detection experiments[752,667,505,507,561,661,290,285,288,753,289,276,676,754,402,689,508,509,691,704,755,664,511,708, 677,…”
mentioning
confidence: 99%